Smart Fish Feeding System for Aquaculture - Sampath T, Senthil Kumar G, Dhanagopal R, Pavanram (International Journal of Control and Automation, 2020)
It’s reported that Aquaculture is a greatly growing industry which contributes to the country's overall white meat requirements. Many steps and measures have been taken for betterment of the production of aquatic organisms in the tanks and ponds, Based on the Third NAP (1998-2010). On developing various automatic fish feeding machines could be very useful and supportive for the development of the aquaculture in our country. This facility was ideated to increase the job opportunity by introducing human controllable semi-automatic drones in fisheries.Semi-automatic feeding system is used for nourishing aquatic creatures in fisheries. The feeder system consists of feeding container held over the polymer cylindrical floats which navigates with the help of two independently rotating turbines.  The semi-automatic controlled feeding system is capable dispensing both the fluid and crystal food pellets into the fish ponds. Entire feeding system can be controlled through the mobile application via wireless networking.